Characteristics of biochar produced from yak manure at different pyrolysis temperatures and its effects on the yield and growth of highland barley. Issue 1 (1st January 2018) - Zhang, Jianghong; Huang, Bing; Chen, Liang; Li, Yang; Li, Wei; Luo, Zhuanxi
ABSTRACT: The yak manure based biochar was produced at different temperatures of 300, 500 and 700 ℃ held for 3 h, which was characterized by BET surface area, X-ray diffraction, Fourier transform infrared  spectroscopy, pH measurement, analysis, scanning electron microscopy and ultimate analysis. The resultant biochar had characteristics of high surface area, high pH, porous structure and rich nutrients such as N, P, Ca, Mg, and K, inferring that the yak manure-derived biochar could be used as a soil conditioner. The field experiment was conducted to study the effect of yak manure derived biochar amendment on the yield and biological traits of highland barley, revealing that adding biochar to soil could increase the yield and growth of highland barley in short-term although the long-term benefits remain to be quantified. The present results can be useful to fill the knowledge gap regarding the potential of yak manure derived biochar to soil improvement.